2017
DOI: 10.1590/s1413-65382317000200005
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação de um Programa de Ensino de Palavras em Libras Utilizando Tecnologia de Realidade Aumentada

Abstract: RESUMO: a Língua Brasileira de Sinais (Libras) é uma língua gestual que abrange as necessidades da comunidade surda e, instituída no Brasil como língua oficial; é ensinada em instituições de atendimento a alunos com surdez. Em vista disso, objetivouse verificar a eficácia na aplicação de um programa de ensino de um grupo de palavras em Libras por meio de um software com tecnologia de realidade aumentada, avaliando o repertório inicial e final de alunos com surdez. Participaram deste estudo oito alunos com idad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 2 publications
0
4
0
7
Order By: Relevance
“…This is considered an interesting finding because it is a key element when considering inclusive education. In this sense, several studies analyzed show the benefits of AR in working with students who have SEN, evidencing the work with the following populations: auditory limitation (Carvalhoand Manzini, 2017), visual limitation (Lin et al, 2016), autism (Tentori et al, 2015), attention deficit hyperactivity disorder (Lin et al, 2016b), dyslexia (Persefoni et al, 2016).…”
Section: Results Reportmentioning
confidence: 95%
“…This is considered an interesting finding because it is a key element when considering inclusive education. In this sense, several studies analyzed show the benefits of AR in working with students who have SEN, evidencing the work with the following populations: auditory limitation (Carvalhoand Manzini, 2017), visual limitation (Lin et al, 2016), autism (Tentori et al, 2015), attention deficit hyperactivity disorder (Lin et al, 2016b), dyslexia (Persefoni et al, 2016).…”
Section: Results Reportmentioning
confidence: 95%
“…Ressaltamos que, sendo a cultura surda essencialmente visual (Quadros, 2006), explorar a Tecnologia como amplificadora sensorial, tal como aponta Souza (2004), configura-se como um caminho viável para o processo de ensino e aprendizagem, pois, "o uso dos recursos tecnológicos pode ampliar os atributos dos estímulos melhorando sua recepção" (Carvalho & Manzini, 2017).…”
Section: Referencial Teóricounclassified
“…Turning the focus of this review to the thematic axes (Figure 3), the six studies that make up the first group have the bias that points to the discussion of the teaching and learning process of written PL for the deaf [4][5][6][22][23][24] . In this group, we identified some studies that sought to present didactic strategies that aimed to facilitate the access of the deaf to written LP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this group, we identified some studies that sought to present didactic strategies that aimed to facilitate the access of the deaf to written LP. Among them, three surveys 4,22,23 have used digital information and communication technologies to achieve this goal, namely: digital book 4 , transposition 22 of some activities proposed in a publication by MEC 25 for the digital sphere and augmented reality 23 for the teaching of words. In the research 4 that used a digital book, the authors concluded that, based on the potentialities arising from the technologies, it is believed that it is possible to produce new meanings in the work with the most diverse language practices in the school context; on the other hand, school practices already considered canonical (and widely diffused and questioned), which in many cases end up being merely reproduced in digital media and evidence school doings that differ greatly from the ways in which children and young people (and the teachers themselves) have been reading and writing in non-school contexts by appropriating the most diverse digital resources 4 .…”
Section: Literature Reviewmentioning
confidence: 99%